Analisis Jejak Sejarah Pemasaran yang dipraktikkan Nabi Muhammad - Mardi, Moh. (LAN TABUR : Jurnal Ekonomi Syariah, 2024)
Historical traces at the time of Rasulallah are more colored about religion and politics but very rarely we encounter in the economic side especially in microeconomic issues related to marketing even though if further examined Rasullah was also a great trader this could be a role model for the world of marketing today, it is very necessary to search for traces of Rasulallah's marketing history with the aim that later it can be used as a guide, reference and also an example for the practice of marketing today. The research method used in this writing is to use the library method by looking for various literature related to Rasullah's marketing. The result of this writing is that the current marketing has been practiced directly by Rasulallah about 1400 years ago and what Rasulallah practiced continues to adapt to any circumstances and anywhere and Rasulallah's activities in marketing can still be used as an example by market players today. Keywords: Marketing, Prophet Muhammad, History